Work Readiness of Select Graduating Students of Mindanao State University Iligan Institute of Technology (Asia Pacific Journal of Social Innovation, 2024)
As thousands of students graduate each year, many findthemselves unemployed because of skills gaps that arebrought about by low work readiness levels. Work readinessis defined as the collection of soft and hard skills thatemplayers require rom job applicants to be employed in aspecific field. Literature claims that skills gap is a result ofa variety of inherent factors in students, and a failure toestablish links between schools and companies to preparestudents with the right skills set currently demanded in theworkplace. In response, this paper studied the workreadiness levels of select graduating students fromMindanao State University Iligan nstitute of Technology(MSU-IIT) to investigate the presence of skills gaps withrespect to the graduating students' profile, and therelationship between such gaps, and the ethnicity and sex ofthe gradua ting students. Findings reveal that there aresignificant differences in the required and perceived workreadiness levels of all Business Management graduating students \, including Visayan, Moro, male and feale, but not for any of the of the computer Studies graduating students. the findings also establish a relationship between the differences noted for all graduating students sample and their ethnicity. Results show that Visayan graduating students tend to have smaller differences or skills gaps, thus have work readiness levels, than Moro graduating students.